-8z-z=-2z-6-4z

Simple and best practice solution for -8z-z=-2z-6-4z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8z-z=-2z-6-4z equation:


Simplifying
-8z + -1z = -2z + -6 + -4z

Combine like terms: -8z + -1z = -9z
-9z = -2z + -6 + -4z

Reorder the terms:
-9z = -6 + -2z + -4z

Combine like terms: -2z + -4z = -6z
-9z = -6 + -6z

Solving
-9z = -6 + -6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '6z' to each side of the equation.
-9z + 6z = -6 + -6z + 6z

Combine like terms: -9z + 6z = -3z
-3z = -6 + -6z + 6z

Combine like terms: -6z + 6z = 0
-3z = -6 + 0
-3z = -6

Divide each side by '-3'.
z = 2

Simplifying
z = 2

See similar equations:

| 490=R-.3R | | -192=-8(1+8m)+8 | | 3x+10x-(6x+8)= | | (x+3i)(x-3i)=9 | | 8x-6=8(x+5) | | -2z-7z=-z-7-4z | | y=1.36x+1.54 | | -2z-7z=-z-4z | | -6/7x | | x=-11+2x | | 2z-7z=5z+6+z | | 3(g-25)=100 | | 3(g-25)= | | 112y+8=2x | | 1/3/5/6= | | 2z-7z=5z+6+2 | | 4x+28=4(x+3)+15 | | 6(-3+5n)=132 | | 3=5(x-2)-(x-5) | | 5=2d-5 | | -10=4y-2 | | 8x+6=4x+54 | | 28=-3f+4 | | 4(5x+7)=-17+5 | | 2g+1=17 | | m^2+9x=-18 | | 3x-2=12+3x | | 5n-8=-28 | | 3(x-2)+2(x+-1)=12 | | 5=2f+5 | | 36=6s+6 | | -11-(-12)=x/5 |

Equations solver categories